HIP/PAP prevents excitotoxic neuronal death and promotes plasticity. (9th October 2014) - Haldipur, Parthiv; Dupuis, Nina; Degos, Vincent; Moniaux, Nicolas; Chhor, Vibol; Rasika, Sowmyalakshmi; Schwendimann, Leslie; le Charpentier, Tifenn; Rougier, Elodie; Amouyal, Paul; Amouyal, Gilles; Dournaud, Pascal; et al.
Abstract Objectives Excitotoxicity plays a significant role in the pathogenesis of perinatal brain injuries. Among the consequences of excessive activation of the N‐methyl‐d‐aspartate (NMDA)‐type glutamate are oxidative stress caused by free radical release from damaged mitochondria, neuronal death and subsequent loss of connectivity. Drugs that could protect nervous tissue and support regeneration are attractive therapeutic options. The hepatocarcinoma intestine pancreas protein/pancreatitis‐associated protein I (HIP/PAP) or Reg3α, which is approved for clinical testing for the protection and regeneration of the liver, is upregulated in the central nervous system following injury or disease. Here, we examined the neuroprotective/neuroregenerative potential of HIP/PAP following excitotoxic brain injury. Methods We studied the expression of HIP/PAP and two of its putative effectors, cAMP‐regulated phosphoprotein 19 (ARPP19) and growth‐associated protein 43 (GAP‐43), in the neonatal brain, and the protective/regenerative properties of HIP/PAP in three paradigms of perinatal excitotoxicity: intracerebral injection of the NMDA agonist ibotenate in newborn pups, a pediatric model of traumatic brain injury, and cultured primary cortical neurons. Results HIP/PAP, ARPP19, and GAP‐43 were expressed in the neonatal mouse brain. HIP/PAP prevented the formation of cortical and white matter lesions and reduced neuronal death and glial activation following excitotoxic insults in vivo. In vitro, HIP/PAP promoted neuronal survival, preserved neurite complexity and fasciculation, and protected cell contents from reactive oxygen species (ROS)‐induced damage. Interpretation HIP/PAP has strong neuroprotective/neuroregenerative potential following excitotoxic injury to the developing brain, and could represent an interesting therapeutic strategy in perinatal brain injury.